The impact of rotary and night work in the context of breast and prostate cancer: a systematic review (Research, Society and Development, 2021)
This work aims to verify in the literature the relationship between cancer and night and shift work. For this, a search was carried out using the PUB MED, WEB OF SCIENCE, SCOPUS and LILACS databases, where 649 studies were found in the last 5 years related to the subject. After going through some exclusion processes, there were only 23 studies that matched the research criteria. In the present work, cohort studies, case-control studies, cross-sectional studies and experimental studies were analyzed, 15 of these studies were about breast cancer, 6 about prostate cancer and 2 about both cancers. Nurses were highlighted as the main research audience. According to the results of this review, it was suggested that night work with interruption of the circadian rhythm may affect and decrease melatonin synthesis, which makes it a worrying fact since low levels of melatonin were closely related to both breast cancer and prostate, and was also classified as having an important antitumor function. Other possible factors related to night work and breast cancer are telomere shortening and risky habits during the night shift. Given the possible risks attributed to these two types of cancer, it is believed that chronotherapy and melatonin-based supplementation would be important measures in the prevention process.